C-reactive protein kinetic as a potential predictive and prognostic factor during treatment with checkpoint inhibitors in R/M-HNSCC - Jungbauer, Frederic; Scherl, Claudia; Rotter, Nicole; Affolter, Annette; Lammert, Anne; Seiz, Elena; Thiaucourt, Margot; Huber, Lena (Cancers, 2024)
Introduction The kinetic of C-reactive protein (CRP) in the early phase of therapy with checkpoint inhibitors (CPI) and its prognostic value has already been investigated in several tumor entities. In particular, flare dynamics have been described as a positive prognostic parameter. The aim of this retrospective study is to examine the extent to which such an application can also be transferred to patients with recurrent or metastatic squamous cell carcinoma of the head and neck region (R/M-HNSCC). Material and Methods All patients treated with CPI for R/M-HNSCC at our clinic between 2018 and 2023 were included (n = 44). Demographic, clinical, histopathologic and laboratory data were extracted from the digital patient records and statistically analyzed. We then examined the CRP kinetic using two previously published classifications and proposed a new classification ourselves. Subsequently, correlation analyses were performed with the overall survival (OS) of the patients. Results Of the two CRP kinetic classifications previously published, only one showed a correlation with the result of the first re-staging, and neither showed a correlation with the OS of R/M-HNSCC patients. Our new CRP kinetic classification showed a significant association with OS in R/M-HNSCC patients (p = 0.05). In a multivariate analysis, our CRP kinetic classification (p = 0.007) and the outcome of the first re-staging (p = 0.002) were significant independent factors for OS. Discussion Our novel CRP kinetic classification significantly correlates with OS in R/M-HNSCC patients, indicating a potential prognostic marker. Existing classifications from other cancer entities showed limited prognostic significance, emphasizing the need for tailored markers. For validation, however, testing on larger R/M-HNSCC patient collectives is necessary.